AKAD SUFTAJAH: PRAKTIK DAN PANDANGAN MAZHAB - Iza Hanifuddin (JURIS (Jurnal Ilmiah Syariah), 2018)
The happening of “Syariah” Funding Committee had to be pushed by transactional agreement to the variety of products. It was done to avoid imitating products that had been created by conventional funding committee. Inovation of product by this commitee was also hoped that it could throw away negative opinion among society that could say that this committee just gave”Syariah” label to a specific product which was already in public market. Therefore, this study was done to push or to interest people to reexplore some other agreements that mostly could be found in classic fiqh hollybook.